Balancing the risks and benefits of antibiotic use in a globalized world: the ethics of antimicrobial resistance - Yusuff Adebayo Adebisi (BMC, 2023)
Abstract Antimicrobial resistance (AMR) is a "silent pandemic" that threatens the efficacy of antibiotics and other antimicrobials. It is imperative to take into account the ethical implications of how these resources are used and distributed as the world deals with this silent pandemic. This commentary discusses the ethical considerations surrounding the use and distribution of antibiotics in the age of resistance, including issues of equity and access, responsibility for antimicrobial stewardship, the environmental impact of antibiotic use, and the development and promotion of these drugs. The ethical implications of unequal access to antibiotics and the role of social determinants of health in shaping this access are considered, as well as the globalization of AMR and the need for multiple stakeholders to be involved in addressing this issue. The opportunities of antimicrobial stewardship programmes for optimising antibiotic use and reducing the emergence and spread of resistant bacteria, as well as the ethical implications of implementing such programmes, are examined. The potential environmental outcomes of antibiotic use and the ethical implications of these impacts are also discussed, as well as the role of the pharmaceutical industry in the development and promotion of these drugs, the potential conflicts of interest that may arise and the ethical dimension of resource transfer from Global North to Global South. This paper emphasises the significance of a holistic strategy to AMR that considers these ethical components, as well as the importance of preserving antibiotic efficacy for future generations.